Laparoscopic transgastric resection for intraluminal gastric gastrointestinal stromal tumors located at the posterior wall and near the gastroesophageal junction - Siow, Sze Li; Mahendran, Hans Alexander; Wong, Cheeming (Elsevier (Singapore) Pte Ltd, 2015)
Objective: Intraluminal gastric gastrointestinal stromal tumors (GISTs) located at the posterior wall and near the gastroesophageal junction represent a surgical challenge. We present our experience of laparoscopic transgastric resection for gastric GISTs of such location. Methods: Data of seven patients undergoing laparoscopic transgastric resection were identified and retrospectively reviewed with regard to procedural steps and patient outcomes. Results: Seven patients (4 men; mean age 64.1 ± 14.6 years) with gastric GISTs underwent laparoscopic transgastric resection from January 2010 to May 2015. Three of the seven GISTs were located near the gastroesophageal junction and the rest were found in the posterior wall of the stomach. All seven patients underwent successful laparoscopic resection without any conversions. There were no mortalities and no significant postoperative complications. Intraoperative endoscopy was performed for all patients. The mean operative time was 164.0 ± 59.1 minutes. Regular diet was resumed within 3 days on average and mean postoperative stay was 3.6 ± 1.3 days. All patients achieved complete R0 resection with a mean tumor size of 5.5 ± 1.1 cm. At a mean follow-up of 48.0 ± 13.4 months, all patients were recurrence free. Conclusions: GISTs of the posterior wall and in close proximity to the gastroesophageal junction can be safely resected laparoscopically using such an approach. Standard technique is required to achieve good oncological outcomes.